Inheritance and Wealth Inequality: Evidence from Population Registers - Mikael Elinder; Oscar Erixson; Daniel Waldenström (Institute for the Study of Labor (IZA), 2016)
We use new population-wide register data on inheritances and wealth in Sweden to estimate the causal impact of inheritances on wealth inequality. We find that inheritances reduce relative wealth inequality (e.g., the Gini coefficient falls by 5–10 percent) but that absolute dispersion increases. Examining different parts of the wealth distribution, we find that the top decile's wealth share decreases substantially, whereas the wealth share of the bottom half increases from a negative to a positive share. In essence, wealthier heirs inherit larger amounts, but less wealthy heirs inherit more relative to their pre-inheritance wealth. We also find that post-inheritance behavioral adjustments mitigate the equalizing effect of inheritances because less wealthy heirs consume larger shares of their inheritances. Moreover, we find that the Swedish inheritance tax reduced the equalizing inheritance effect but that the redistribution of tax revenues could reverse this result. Finally, we show that inheritances increase wealth mobility.
Keywords: H24; D63; E21; 330; bequests; estates; net worth; inheritance taxation; wealth distribution